KEMAMPUAN PESERTA DIDIK MENYELESAIKAN SOAL CERITA MATERI VOLUME KUBUSDAN BALOK MENGGUNAKAN LANGKAH POLYADI KELAS V SEKOLAH DASAR - angike ladesta (Jurnal Inovasi Sekolah Dasar, 2019)
Abstract:This study was aimed to improve the ability of students to solve the mathematics word problems of the volume of cubes and cuboids using Polya’s steps in the 5th gradesof SD Negeri 24 Palembang. This type is Classroom Action Research. The data were collected by usingtests and observation. The results of the study showed that using the Polya’s steps can improve the ability of students to solve the mathematics word problems of the volume of cubes and cuboids. It can be seen from the learning completeness of the students in the first cycle with a percentage of 58.3%, the second cycle increased to76% and the third cycle increased to 92%.These findings also supported by the result observations of thestudentsactivities that improvement in all cycles. Furthermore, it can be concluded that using the Polya’s steps can improve the ability of students to solve mathematics word problems about the volume of cubes and cuboids in the 5th gradesof SD Negeri 24 Palembang.Keywords:Polya’s steps, abilityto solve word  problems, volume of cubes and cuboids. Abstrak:Penelitian ini bertujuan untuk meningkatkan kemampuan peserta didik dalam menyelesaikan soal cerita materi volume kubus dan balok menggunakan langkah Polya di kelas V SD Negeri 24 Palembang. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Teknik pengumpulan data yang digunakan yaitu tes dan observasi. Hasil penelitian menunjukkan bahwa penggunaan langkah Polya dapat meningkatkan kemampuan peserta didik dalam menyelesaikan soal cerita materi volume kubus dan balok. Hal ini terlihat dari ketuntasan belajar peserta didik pada siklus I dengan persentase sebesar 58,3%, siklus II meningkat menjadi 76% dan siklus III meningkat menjadi 92%. Hal ini didukung pula dengan hasil observasi aktivitas peserta didik yang juga meningkat disetiap siklusnya. Jadi, dapat disimpulkan bahwa dengan menggunakan langkah Polya dapat meningkatkan kemampuan peserta didik dalam menyelesaikan soal cerita matematika materi volume kubus dan balok di kelas V SD Negeri 24 Palembang.Katakunci: langkah Polya, kemampuan menyelesaikan soal cerita, volume  kubus dan balok